Relationship between HLA-DRB1 alleles and onychomycosis in Chinese Han population in Guangdong province - Yu LAN; Bo-wen ZHENG; Sha LU; Xi-qing LI; Jun-min ZHANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2020)
Objective: To investigate the relationship between polymorphism of human leukocyte antigen (HLA)-DRB1 alleles and onychomycosis in Chinese Han population in Guangdong province. Methods: Polymerase chain reaction-sequence specific primers (PCR-SSP) technique was adopted to detect the allele frequencies of HLA-DRB1 in 64 cases of onychomycosis, including 10 cases of Trichophyton rubrum infection, and 64 healthy controls. The differences in allele frequencies were compared between patients and controls. Results: The allele frequencies of HLA-DRB1*10 in Han patients with onychomycosis were higher than that in the controls (χ2=5.10, P<0.05). In contrast, the allele frequencies of HLA-DRB1*12 in Han patients with trichophyton rubrum infection were lower than that in the controls (χ2=4.70, P<0.05). Conclusions: HLA-DRB1*10 alleles may be the susceptibility gene of onychomycosis in Chinese Han population in Guangdong province. HLA-DRB1*12 alleles could prevent the development of onychomycosis caused by trichophyton rubrum. HLA alleles could be immunogenetically associated with onychomycosis.